Operation of ultra-high voltage (>10kV) SiC IGBTs at elevated temperatures: Benefits & constraints - Tiwari, Amit K.; Udrea, Florin; Lophitis, Neophytos; Antoniou, Marina (My University, 2019)
State of the art TCAD simulation models are used to simulate the performance of ultra-high voltage (10-20 kV) SiC IGBTs in the temperature range 300-775 K. We show that unlike Si-based counterparts, ultra-high voltage SiC IGBTs stand to gain from the temperature rise if the limit is not exceeded. We show that whilst an operation at 375 K is highly promising to achieve the most optimum on-state characteristics from SiC IGBTs, no significant degradation in the on-state current and breakdown voltage alongside with negligible rise in leakage current is observed until 550 K. Therefore, ≥10 kV SiC IGBTs are highly promising for Smart Grid and HVDC.
Keywords: Elevated Temperatures; HVDC and Smart Grid; SiC IGBT; Ultra-high voltage